(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Women’s rights concerns and child abuse are two of the most visible problems that India faces even in the twenty-first century. This study explains how the most serious violation of essential freedoms in India is the mistreatment of women and children. The present study examines the factors that contribute to women’s difficulties and child abuse in India, as seen through the lens of Arundhati Roy’s smart novel The God of Small Things. Sex segregation and child abuse in Indian culture remain the best case scenario in today’s India, even after independence. An Indian lady’s life is full with many responsibilities and duties that she fulfils in her roles as a wife, daughter-in-law, mother, or all of the above. She’s been told from the outset that her torments and torments are aware of her modesty, and that she should try to satisfy others rather than herself. She must be able to remain firm in the face of adversity and maintain her composure while overcoming the different challenges she faces during her life. This is the enigma of a woman’s eventual emergence as a survivor